Demographic processes in rural areas of Belarus: geographical structure and spatial dynamics - Antipova, Ekaterina; Fakeyeva, Liudmila (Bulletin of Geography. Socio-economic Series, 2012)
The study presents the spatiotemporal regularities and shifts in geo-demographic development of rural areas of Belarus at the multiscale level. Trends in rural population size dynamics for the period of 1959-2009 are detected and characterised. In accordance with the trends in the dynamics of the rural population of Belarus spatial regularities were identified. The geo-demographic territory of Belarus is typified on character of demographic dynamics and natural movement processes of rural population. We have identified three types of districts by the nature of the rural population dynamics for the period of 1970-2009: stable, growing and shrinking; and three types of natural population movement dynamics for the same period in accordance with spatial and temporal heterogeneity of the rural depopulation.